Left ventricular hypertrophy in athletes: Differentiating physiology from pathology - Augustine, D. X.; Howard, L. (Current Treatment Options in Cardiovascular Medicine, 2018)
Purpose of review: The changes that occur in athlete`s heart are influenced by a number of factors including age, gender, ethnicity and the type of cardiovascular training. It is therefore important that the clinician is able to integrate all of these factors when assessing athletes to be able to guide investigations appropriately and to distinguish pathology from physiology. This review discusses the potential diagnostic conundrums when trying to differentiate physiological left ventricular hypertrophy from pathological hypertrophic cardiomyopathy in athletes. The mechanism of physiological and pathological hypertrophy is discussed together with history, clinical and investigational findings that can help to identify pathology. Recent findings: Athletes with hypertrophic cardiomyopathy are more likely to have non-concentric left ventricular hypertrophy (LVH), an elevated relative wall thickness, lateral ECG changes and a smaller LV cavity than athletes with physiological LVH. Certain diastolic echocardiographic parameters when used as part of an algorithm (e'; E/E'; E/A) can help to distinguish physiology from pathology, and there is evidence that assessment of global longitudinal strain during exercise echocardiography may be of use in the future. Cardiac MRI is an important imaging modality that can have an additive effect over echocardiography in the diagnosis of cardiomyopathy. Late gadolinium enhancement is a recognised advantage for cardiac magnetic resonance to allow detection of fibrosis in hypertrophic cardiomyopathy. T1 mapping and extracellular volume quantification may be a tool for the future to help distinguish athlete`s heart from HCM. Summary: Cardiac adaptation to exercise and training in athletes, the athlete`s heart causes electrophysiological and geometric changes that may mimic mild phenotypes of a pathological cardiomyopathy. This review article summarises a systematic approach to the assessment of left ventricular hypertrophy in athletes and describes pertinent clinical and investigation findings that can help to differentiate physiology from pathology.